2015
DOI: 10.2174/1874210601509010060
|View full text |Cite|
|
Sign up to set email alerts
|

Variable Torque Prescription: State of Art.

Abstract: The variable prescription is widely described under the clinical aspect: the clinics is the result of the evolution of the state-of-the-art, aspect that is less considered in the daily literature. The state-of-the-art is the key to understand not only how we reach where we are but also to learn how to manage propely the torque, focusing on the technical and biomechanical purpos-es that led to the change of the torque values over time. The aim of this study is to update the clinicians on the aspects that affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…Biomechanically, the torque is represented by the torsion of a rectangular archwire in the bracket slot. 3 The earliest forms (first generation) of aligner systems were solely reliant on the aligner to achieve their results. No auxiliary elements were incorporated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomechanically, the torque is represented by the torsion of a rectangular archwire in the bracket slot. 3 The earliest forms (first generation) of aligner systems were solely reliant on the aligner to achieve their results. No auxiliary elements were incorporated.…”
Section: Discussionmentioning
confidence: 99%
“…For simulation of the involved structures, their physical characteristics were determined in the following manner: Alveolar bone: A linear elastic, isotropic, and homogeneous behaviour was assumed and mechanical properties were obtained from cancellous bone values taken from previous studies. Differences in rigidity between different bone types were not contemplated, as they were not considered relevant to the objectives of the study (Young modulus of 1.37 × 10 3 ). Teeth: A linear elastic, isotropic, and homogeneous behaviour was assumed and mechanical properties were obtained from previous studies. Differences in rigidity among enamel, dentin, and cement were not contemplated, as they were not considered relevant to the objectives of the study (Young Modulus of 1.96 × 10 4 ). Composite attachments: Assumed as an isotropic homogeneous linear elastic behaviour, with mechanical properties referred by the manufacturers (Filtek TMP60, 3M ESPE, 3M, St. Paul, MN) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is currently a great range of prescriptions available to the orthodontist 10 , including prescriptions customized for each case 11 , one should still apply archwire torsion forces to obtain the desire torque 12,13 . Some studies have shown that the application of high torque (third-order folds) can fracture ceramic brackets 7,[14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Ceramics have high friability (no plastic deformation), but also have a high resistance to weariness and corrosion and excellent optical properties 6 . Several factors can influence the torque during orthodontic mechanics, which include the torsion magnitude, wire composition and thickness, slot size and depth, vertical positioning, and bracket 17,18 . This phenomenon occurs more frequently in anterior teeth 10,16 and at the base of the bracket wings, where most tension is present, due to archwire torsion forces inside the slot 19 . The addition of wires and accessories may induce the development and propagation of cracks in the brackets 19 .…”
Section: Introductionmentioning
confidence: 99%